Characterization of ethylene-propylene-diene terpolymers using high-temperature size exclusion chromatography coupled with an ultraviolet detector. (1st March 2022) - Deshmukh, Subrajeet; Brüll, Robert; Macko, Tibor; Arndt, Jan-Hendrik; Bernardo, Raffaele; Niessen, Sander
Abstract: The distribution of the pendant double bond along the molar mass axis impacts the vulcanization behavior of ethylene-propylene-diene (EPDM) terpolymers. Yet, the analysis of this parameter has so far been hampered by the lack of suitable detection methods. Towards this goal we have investigated the potential of ultraviolet detector (UV) detection for high temperature size exclusion chromatography of EPDM terpolymers containing 5-ethylidene-2-norbornene (ENB), dicyclopentadiene (DCPD), and vinyl norbornene (VNB) as termonomer. The influence of termonomer structure and experimental parameters such as, mobile phase, analyte concentration and temperature on the spectroscopic response was probed. EPDM containing ENB showed a significantly stronger UV-absorption compared to terpolymers with VNB and DCPD. The absorbance was found to correlate with the sample concentration approaching signal saturation at higher ENB content. Generally, temperature did not have any significant effect on the UV absorbance of EPDM. Based on the results, a method was developed, which can profile the content of ENB along the molar mass axis. An evaporative light scattering detector (ELSD) was employed to monitor the analyte concentration, in combination with the UV detector, to quantitatively measure the distribution of ENB content along the molar mass distribution. This work could be feasible for the other two commercial relevant termonomers DCPD and VNB. Graphical abstract: Image 1 Highlights: UV absorption of ethylene propylene diene (EPDM) terpolymers was investigated. The influence of experimental parameters on the spectroscopic response was probed. UV-absorption varied significantly for different types of dienes in EPDM. A method was developed to measure the content of ENB along the molar mass axis.